Intro to MSE - Cost - Kitto, Kathleen (McGraw-Hill Education, 2018)
This DataVis project is part of a series of 10 projects designed for an Introduction to Materials Science and Engineering course. Students should download the project document below and then access the project in DataVis to complete the project.